The effects of cultural engagement on health and well-being: a systematic review - Viola, Erica; Martorana, Marco; Ceriotti, Daniele; De Vito, Marta; De Ambrosi, Damiano; Faggiano, Fabrizio (Frontiers in Public Health, 2024)
Purpose This paper examines the effectiveness of culture-based activities in improving health-related outcomes among middle-aged and older adults. Based on the biopsychosocial model, this review aims to explore the impact of cultural engagement on health and well-being. Methods We conducted a systematic literature review based on peer-reviewed articles retrieved from various electronic databases. In total, 11 studies were included in this review. Our study population consisted of healthy adults aged over 40 years. Results The results provide evidence of positive association between cultural participation and better mental health (e.g., cognitive decline, depression, anxiety), frailty, resilience, well-being and social relations. Conclusion This review suggests that cultural engagement serves as an effective means for individuals to maintain and enhance their health and well-being. The field is mostly limited by the heterogeneity of the studies and poor conceptualization of cultural activities. Thus, it is recommended that future research consider the effects of different cultural interventions in developing effective strategies for promoting healthy lifestyles and enhancing quality of life in later stages of life.